2006
DOI: 10.1200/jco.2005.04.1053
|View full text |Cite
|
Sign up to set email alerts
|

Fulvestrant in Women With Advanced Breast Cancer After Progression on Prior Aromatase Inhibitor Therapy: North Central Cancer Treatment Group Trial N0032

Abstract: Fulvestrant is a well-tolerated treatment and has efficacy against breast cancers that have progressed after therapy with a third-generation AI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(82 citation statements)
references
References 14 publications
5
77
0
Order By: Relevance
“…The incidence of thromboembolic events was higher in patients receiving fulvestrant in this study (5.8 vs 3.3%), but not significantly so (PZ0.22). This apparent increase in thromboembolic events was not noted in the other phase III trials of fulvestrant (Howell et al 2002, Osborne et al 2002) and no thromboembolic events were reported in two recent phase II studies (Ingle et al 2004, Perey et al 2004. Three patients receiving fulvestrant withdrew because of a drug-related AE (cerebrovascular accident, deep vein thrombosis and pulmonary embolus (one patient each)).…”
Section: Tolerability Of Pure Oestrogen Antagonistsmentioning
confidence: 70%
See 1 more Smart Citation
“…The incidence of thromboembolic events was higher in patients receiving fulvestrant in this study (5.8 vs 3.3%), but not significantly so (PZ0.22). This apparent increase in thromboembolic events was not noted in the other phase III trials of fulvestrant (Howell et al 2002, Osborne et al 2002) and no thromboembolic events were reported in two recent phase II studies (Ingle et al 2004, Perey et al 2004. Three patients receiving fulvestrant withdrew because of a drug-related AE (cerebrovascular accident, deep vein thrombosis and pulmonary embolus (one patient each)).…”
Section: Tolerability Of Pure Oestrogen Antagonistsmentioning
confidence: 70%
“…Furthermore, a phase II trial has shown that of 67 patients who developed resistance initially to tamoxifen and then to an AI, 28.4% subsequently gained CB (CR C PR C SD R24 weeks) with fulvestrant (median treatment duration 3.8 months) (Perey et al 2004). Similarly, in another phase II trial of 77 patients with advanced breast cancer who had progressed on prior AI therapy (21 had also received tamoxifen), 32.5% gained CB with fulvestrant (Ingle et al 2004(Ingle et al , 2006. Additionally, in the compassionate-use programme, CB was achieved in patients who received fulvestrant after progression on prior endocrine therapies, including both AIs and SERMs (Petruzelka et al 2004, Steger et al 2005.…”
Section: Future Directionsmentioning
confidence: 99%
“…Several clinical studies have shown similar efficacy for fulvestrant compared with AIs together with a consistently good tolerability profile (Howell et al, 2002(Howell et al, , 2004(Howell et al, , 2005Osborne et al, 2002;Robertson et al, 2003;Ingle et al, 2006;Gradishar et al, 2007;Chia et al, 2008). However, no clinical studies have been conducted that address the issues of effectiveness and cost effectiveness of different treatment sequencing options for women with HR ĂŸ advanced breast cancer -a very important question, given standard clinical practice for treating advanced breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Fulvestrant is licensed in the United Kingdom for the treatment of postmenopausal women with oestrogen-receptor positive, metastatic breast cancer whose disease has progressed or relapsed on or after previous antioestrogen therapy. Several clinical studies have confirmed that fulvestrant is at least as effective as AIs in the treatment of advanced breast cancer in patients with HR ĂŸ disease (Howell et al, 2002(Howell et al, , 2004(Howell et al, , 2005Osborne et al, 2002;Robertson et al, 2003;Ingle et al, 2006). In addition, clinical evidence shows that the addition of fulvestrant into a sequence of well-tolerated hormonal therapies can be undertaken without a detrimental effect on responses to subsequent treatments Howell et al, 2005).…”
mentioning
confidence: 99%
“…Unfortunately, treatment options are limited when patients experience either progression or recurrence on non-steroidal AIs. There have been limited data to support the activity of both fulvestrant and exemestane in this setting, suggesting a lack of cross-resistance between these treatments and the nonsteroidal AIs [7][8][9][10][11]. Thus, there is an increasing need for alternative and effective treatments that can be used after non-steroidal AI failure, particularly in patients with VM, who are generally considered difficult to treat.…”
Section: Introductionmentioning
confidence: 99%